Leadership Dynamics and Organizational Advancement in Non-Formal Education: A Case Study of PKBM Karya Manunggal - Nurazizi, Najwa; Sari, Della Puspita; Akmalina, Habillah Safira (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2024)
Purpose – This study examines leadership practices at PKBM Karya Manunggal to understand how leadership influences the success of non-formal education institutions. Design/methods – A qualitative case study approach was used, employing in-depth semi-structured interviews with the head of the institution. Data were analyzed thematically, and member checking was applied to ensure data validity and reliability. Findings – Inclusive and participatory leadership practices contributed to operational development, improved facilities, increased student enrollment to 78, and graduate success, despite challenges such as low student engagement, accreditation difficulties, and limited tutor involvement. Research implications/limitations – The focus on a single institution limits the generalizability of the results, suggesting the need for broader comparative studies across non-formal education centers. Practical implications – The findings highlight the importance of professional development, technological integration, curriculum enhancement, community engagement, and alumni network development to strengthen institutional sustainability. Originality/value – This study offers original insights into leadership strategies in Indonesian non-formal education and provides actionable recommendations for strengthening educational equity and institutional resilience.